Learning from appropriation practices: Towards the next generation of e-participation environments enabling collaborative writing in-situ and ex-situ. Issue 1 (3rd April 2018) - Al Zubaidi-Polli, Anna Maria; Verdezoto, Nervo
Abstract : Purpose: Public participation is an important – if not the most important – pillar of democracy. When designing new e-participation environments, it is advisable to consider previous appropriation practices of deliberative community networks to encourage broad participation. This can be achieved by sharing appropriation practices and by supporting the situated development of use, which may not only increase user participation but also decrease user frustration. Design/methodology/approach: This paper addresses previously analyzed e-participation appropriation practices and technological limitations that participants faced when using the e-participation environment from the Aarhus's Artwork design experiment. The lessons learned from these limitations and the appropriation practices identified help us in designing the next generation of e-participation environments and in counteracting their unsuccessful appropriation. Findings: Potential design improvements for future collaborative writing e-environments that facilitate location-agnostic participation, and improvements that enable successful technology appropriation are presented. Originality/value: These improvements are important to future research to inform a hybrid of in situ and ex situ technologies that enable collaborative writing to increase public participation in leisure spaces, engage a broader range of citizens and thus also encourage less motivated people.